Housing-Consumption Channel of Mortgage Demand - Gabriel M. Ahlfeldt; Nikodem Szumilo; Jagdish Tripathy (CESifo GmbH, 2024)
We quantify the housing-consumption channel in mortgage demand according to which households borrow more following house-price increases since housing and non-housing consumption are imperfect substitutes. To identify this channel, we take a structural approach to mortgage demand and supply, exploiting exogenous variation in house-price growth and a unique dataset with matched transaction-price and mortgage information. We estimate an elasticity of mortgage borrowing to house-prices of 0.82. Counterfactual analysis of the general-equilibrium of housing and mortgage markets shows that, sans housing-consumption channel, mortgage and house-price growth in the UK would have been 50% and 31% lower, respectively, since the 1990s.
Keywords: G11; G21; R21; 330; house prices; mortgage demand; housing consumption; consumption channel; property taxes